Impelementasi Kode Etik Jurnalistik Dalam Peliputan Berita Kriminal Wartawan Jatimnow.com - Shella Shofiyannajah; Suprihatin; Moch. Subechi Nurcahyo (DIGICOM : Jurnal Komunikasi dan Media, 2023)
This research is a study that examines the application of a journalistic code of ethics by Jatimnow.com journalists who carry out their journalistic duties in crime news. This study uses a qualitative method with a descriptive approach. The data comes from interviews with journalists, observations, and documentation from the online media Jatimnow.com. This study aims to find out how Jatimnow.com journalists apply the journalistic code of ethics to criminal news. Journalists are people whose job is to cover news in the media. Like other professions, journalists have a journalistic code of ethics that serves as a guide and a set of rules that must be applied in carrying out their duties in the field. The existence of a journalistic code of ethics makes news reliable for its truth and quality. Crime news is directly related to crime events that occur daily in society. The existence of extraordinary crimes that make criminals who are included in extraordinary crimes have special treatment, and Child Friendly Reporting Guidelines that journalists must pay attention to. The results of this study indicate that Jatimnow.com journalists have applied a journalistic code of ethics to criminal news. However, it was found that there were differences in the application of Article 2, namely, respecting the experience of the informants in presenting images in every criminal case that occurred. Because a recidivist perpetrator is considered the information must be known to the wider community in order to avoid the crime being repeated.